Microstructures and Mechanical Properties of Low Carbon Steel Hot Rolled in Ferrite Region Based on CSP Line. Issue 7 (2nd April 2019) - Hu, Xuewen; He, Guoning; Peng, Huan; Jiang, Bo; Zhang, Chaolei; Liu, Yazheng
Abstract : In this paper, the effect of ferrite region rolling on the microstructure and properties of steel plate heat commercial (SPHC) steel produced by compact strip production (CSP) process was studied in detail. Comparing ferrite rolled sheet with austenite rolled sheet, it was found that the average ferrite grain size of low carbon steel sheet rolled in ferrite region increased from 10.6 to 27.6 µm and the dislocation density was slightly reduced from 1.79 × 10 11 to 8.9 × 10 10  cm −2 . The yield strength of ferrite rolled sheet is 92 MPa lower than that of austenite rolled sheet. The theoretical calculation and experimental results indicates that the coarsening of grains contributes to the 70% reduction of yield strength of ferrite rolled sheet, and the reduction of dislocation density and other strengthening factors account for about 30%. Texture analysis results by electron backscattered diffraction (EBSD) shows that the growth of {001} <110> and {112} <110> component in the texture of ferrite rolled sheet lead to the reduction of r ¯ and Δ r . Abstract : Comparing ferrite rolled sheet with austenite rolled sheet, the average ferrite grain size of low carbon steel sheet rolled in ferrite region increases and the dislocation density is slightly reduced. The coarsening of grains contributes to the 70% reduction of yield strength of ferrite rolled sheet, and the reduction of dislocation density and other strengthening factors accounts for about 30%.